Directing Remittances to Education with Soft and Hard Commitments : Evidence from a Lab-in-the-Field Experiment and New Product Take-up among Filipino Migrants in Rome - De Arcangelis, Giuseppe (World Bank, Washington, DC, 2014)
This paper tests how migrants' willingness to remit changes when given the ability to direct remittances to educational purposes using different forms of commitment. Variants of a dictator game in a lab-in-the-field experiment with Filipino migrants in Rome are used to examine remitting behavior under varying degrees of commitment. These range from the soft commitment of simply labeling remittances as being for education, to the hard commitment of having funds directly paid to a school and the student's educational performance monitored. The analysis finds that the introduction of simple labeling for education raises remittances by more than 15 percent. Adding the ability to directly send this funding to the school adds only a further 2.2 percent. The information asymmetry between migrants and their most closely connected household is randomly varied, but no significant change is found in the remittance response to these forms of commitment as information varies. Behavior in these games is shown to be predictive of take-up of a new financial product called EduPay, designed to allow migrants to pay remittances directly to schools in the Philippines. This take-up seems largely driven by a response to the ability to label remittances for education, rather than to the hard commitment feature of directly paying schools.